Institutional Parameters of a Region-Wide Economic Agreement in Asia: Examination of Trans-Pacific Partnership and ASEAN+α Free Trade Agreement Approaches - Shintaro Hamanaka (Asian Development Bank (ADB), 2010)
The future creation of a region-wide economic agreement in Asia has become the hot issue among trade policymakers in the region. The APEC 2010 Summit Statement clearly states that the members should pursue a Free Trade Area of the Asia-Pacific (FTAAP), building on various ongoing regional cooperation formworks including ASEAN+3 or +6 and the Trans-Pacific Partnership (TPP). This paper considers the path or sequencing towards a future region-wide economic agreement in Asia, both theoretically and empirically. It attempts to streamline the policy arguments on the sequencing issues by clarifying the pros and cons of various approaches. The paper first presents two possible approaches to a region-wide economic agreement: the consolidation approach and the expansion approach. It then reviews political economy theories on the evolution of economic agreements with regard to four key issues to highlight the differences between the two approaches: (i) negotiation timing, (ii) negotiation format, (iii) broader–deeper trade-off, and (iv) the participation process. The final section of the paper analyzes and considers three existing economic agreements—ASEAN+ free trade agreements, the TPP, and the Asia–Pacific Trade Agreement—that have the potential to be the basis of a future region-wide economic agreement.
hdl:11540/1939
Keywords: F15; F53; F55; F59; 330; Trans-Pacific Partnership Agreement (TPP); Free Trade Area of the Asia-Pacific (FTAAP); ASEAN+3 FTA; ASEAN+6 FTA; Consolidation Approach; Expansion Approach